ANALISIS VARIABEL-VARIABEL PENENTU PREDIKAT BANK UMUM DI INDONESIA - Sugiarto Sugiarto (STIE Wiyatamandala, 2017)
The predicate of banks operating in Indonesia is influenced by the performance and quality of banks. Predicates held by banks should be closely correlated with the ability of each banking institution to maintain high competitiveness. Infobank Research Bureau classifies banks operating in Indonesia in four predicates, that are very good, good, quite good, and not good. In this study, the predicate of bank are classified into two groups, namely very good and not very good. Banks that are classified in the predicate good, quite good, and not good according to the Infobank Research Bureau are united into a group of banks with predicate not very good. This research was conducted to find variables that becomes significant determinant for the predicate of banks operating in Indonesia. The study was conducted using secondary data obtained from Infobank (2015). Overall there were 99 banks evaluated. As the research variables were Category of Bank’s book, Composite risk management profile (RMP_CG), Good Corporate Governance composite profile (GCG_CG), Non-Performing Loan (NPL), Net Interest Margin (NIM), Core capital (CoreCap), Return on Assets (ROA), Return on Equity (ROE), Profit Growth (PrGrowth), and Ratio of Operating Expenses to Operating Income (BOPO). Tests were performed using Logistic Regression Analysis. The results obtained indicate that predicate classification of banks are affected by variables Composite risk management profile, Non-Performing Loan, and Return on Assets. The accuracy of the predictions of the model is 92.9 %.